Capital Structure–Firm Performance Nexus: The Moderating Effect of Board Independence - Imani Mokhtar; Ismah Osman; Fatimah Setapa; Nur Afizah Muhamad Arifin; Roslina Mohamad Shafi; Ruhaini Muda (Information Management and Business Review, 2023)
The purpose of this study is to investigate the relationship between capital structure and firm performance by exploring the moderating effect of one of the corporate governance mechanisms, namely board independence. Panel data regression was employed based on a sample of 492 non-financial listed companies in Malaysia from 2010 to 2019. The results showed that capital structure has a significant positive impact on firm performance. Meanwhile, board independence significantly and negatively moderates the relationship between capital structure and firm performance. The findings of this study shall provide better insights for investors, firm managers, and policymakers on the critical role of corporate governance mechanisms in enhancing firm performance, particularly in implementing suitable actions and policies.